Synthesis of Azido and Triazolyl Purine Ribonucleosides. Issue 9 (7th September 2021) - Līpiņš, Dāgs Dāvis; Jeminejs, Andris; Novosjolova, Irina; Bizdēna, Ērika; Turks, Māris
Abstract: Here, we describe detailed synthetic protocols for preparation of 6‐amino/thio‐2‐triazolylpurine ribonucleosides. First, 9‐(2′, 3′, 5′‐tri‐ O ‐acetyl‐β‐D ‐ribofuranosyl)‐2, 6‐diazido‐9 H ‐purine, to be used as a key starting material, is synthesized in an SN Ar reaction with NaN3 starting from commercially available 9‐(2′, 3′, 5′‐tri‐ O ‐acetyl‐β‐D ‐ribofuranosyl)‐2, 6‐dichloro‐9 H ‐purine. Next, 2, 6‐bis‐triazolylpurine ribonucleoside is obtained in a CuAAC reaction between diazidopurine derivative and phenyl acetylene, and used in SN Ar reactions with N ‐ and S ‐nucleophiles. In these reactions, the triazolyl ring at the purine C6 position acts as a good leaving group. Cleavage of acetyl protecting groups from the ribosyl moiety is achieved in presence of piperidine. In the SN Ar reaction with amino acid derivatives, the acetyl groups remain intact. Moreover, 9‐(2′, 3′, 5′‐tri ‐O ‐acetyl‐β‐D ‐ribofuranosyl)‐2, 6‐diazido‐9 H ‐purine is selectively reduced at the C6 position using a CuSO4 ·5H2 O/sodium ascorbate system. This provides a straightforward approach for synthesis of 9‐(2′, 3′, 5′‐tri ‐O ‐acetyl‐β‐D ‐ribofuranosyl)‐6‐amino‐2‐azido‐9 H ‐purine. © 2021 Wiley Periodicals LLC Basic Protocol 1 : Synthesis of 6‐amino‐2‐triazolylpurine ribonucleosides Basic Protocol 2 : Synthesis of 6‐thio‐2‐triazolylpurine ribonucleosides Basic Protocol 3 : Synthesis of 6‐amino‐2‐azidopurine ribonucleoside